High-stability medical polypropylene patch as well as preparation method and application thereof
By forming a composite hydrogel coating of polyvinyl alcohol and methacrylated hyaluronic acid on the surface of polypropylene patches, the postoperative adhesion problem caused by polypropylene patches is solved, the pore structure is maintained and tissue repair is promoted, and high stability is achieved and anti-adhesion effects.
Patent Information
- Application Number
- CN202411315155.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
Polypropylene patches lead to postoperative adhesions during abdominal wall hernia surgery. The use of existing hydrogels will damage the pore structure of the patch and affect tissue integration.
A composite hydrogel of polyvinyl alcohol and methacrylated hyaluronic acid is used to form a hydrophilic coating on the surface of the polypropylene patch by ultraviolet light-induced radical polymerization and freeze-thawing method to maintain the pore structure and improve the anti-adhesion effect.
It achieves a high-stability anti-adhesion effect, reduces inflammatory response, promotes neovascularization, and maintains the integration of patches and tissues during postoperative tissue repair.
Smart Images

Figure CN119280493A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a medical polypropylene patch for preventing postoperative adhesion, and in particular to a highly stable medical polypropylene patch obtained by combining a polyvinyl alcohol and methacrylated hyaluronic acid composite hydrogel with a polypropylene patch. Background Art
[0002] During the surgical treatment of abdominal wall hernia, polypropylene (PP) patches are usually used to repair the weak parts of the abdominal wall defect. However, the surface hydrophobicity and foreign body sensation of the patch can cause the body to produce an immune response, leading to excessive adhesion of fibroblasts and a large amount of deposition of collagen fibers, which in turn causes abdominal adhesions and even recurrence of hernia in severe cases. At present, researchers have alleviated the postoperative adhesion phenomenon to a certain extent by using a combination of hydrogel and polypropylene patches. However, the use of hydrogel will cause the loss of the pore structure of the polypropylene patch itself. The porous polypropylene patch is conducive to the ingrowth of tissues and integration with host tissues, promoting the repair of damaged tissues. Therefore, it is necessary to develop a polypropylene patch with anti-adhesion properties while retaining the pore structure of the patch.
[0003] Hyaluronic acid (HA) is a naturally occurring non-sulfonated glycosaminoglycan with moisturizing and anti-adhesive properties. It is widely used in the field of postoperative adhesion prevention. The carboxyl or hydroxyl groups on the HA molecular chain are easily modified, and the modified HA can form hydrogels in a variety of ways. Among them, photo-crosslinked HA-based hydrogels have the advantages of in-situ molding and easy adjustment. They can form a gel coating in situ on the surface of polypropylene monofilaments, which is conducive to retaining the pore structure of the patch. However, HA is easily hydrolyzed or enzymatically degraded in the body and cannot fully exert its anti-adhesion effect. Polyvinyl alcohol (PVA) is a synthetic water-soluble polymer approved by the US Food and Drug Administration for clinical use. The polyvinyl alcohol hydrogel formed by the freeze-thaw method has good biocompatibility, excellent stability and physical and mechanical properties, and has been used in the fields of postoperative adhesion prevention, wound repair, bone tissue engineering, etc. Summary of the invention
[0004] Purpose of the invention: When a hydrogel coating is applied to the surface of a polypropylene hernia patch material, the pore structure of the material itself will be affected, resulting in reduced tissue integration after surgery. In order to reduce this effect, the purpose of the present invention is to provide a highly stable medical polypropylene patch, a preparation method thereof, and an anti-adhesion use thereof. Polypropylene is used as a substrate, and a hydrophilic composite hydrogel coating is prepared on its surface. The hydrogel coating uses polyvinyl alcohol and methacrylated hyaluronic acid as raw materials, and forms a hydrogel on the surface of a polypropylene monofilament by ultraviolet light-induced free radical polymerization and freeze-thaw methods. An anti-adhesion patch with a coating of good stability is obtained, which solves the problem of postoperative adhesion after a polypropylene patch is implanted in the body.
[0005] Technical solution: In order to achieve the above-mentioned invention object, the present invention adopts the following technical solution: A highly stable medical polypropylene patch comprises: a substrate and a hydrophilic composite hydrogel coating coated on the surface of the substrate; The substrate is mesh polypropylene; the hydrogel coating is prepared from polyvinyl alcohol and methacrylated hyaluronic acid by ultraviolet light-induced free radical polymerization and freeze-thaw method.
[0006] The preparation process of the methacrylated hyaluronic acid is as follows (Growth factor–loaded sulfated microislands in granular hydrogels promote hMSCs migration and chondrogenic differentiation Acta Biomaterialia 166 (2023) 69-84; Anna Puiggalí-Jou et al.): (1) Dissolving hyaluronic acid in a solvent at room temperature to 50° C.; adjusting the pH value to 7.5 to 9 to obtain a hyaluronic acid solution; The solvent is water or phosphate buffer solution; the pH regulator is 5 mol / L sodium hydroxide solution.
[0007] (2) Add methacrylic anhydride to the hyaluronic acid solution, stir and react for 8 to 24 hours in an ice bath, then drop ice ethanol into the solution for precipitation, and then centrifuge in a high-speed centrifuge for 10 minutes to remove the supernatant to obtain a precipitate.
[0008] (3) The obtained precipitate is placed in a dialysis bag and dialyzed in water. After the dialysis is completed, the precipitate is freeze-dried to obtain a sponge-like solid methacrylated hyaluronic acid.
[0009] The preparation process of high-stable medical polypropylene patch is as follows: Step 1: Preparation of gel precursor solution: prepare methacrylated hyaluronic acid solution at 50°C; prepare polyvinyl alcohol solution at 80°C; mix the two solutions in proportion to obtain a gel precursor solution; the concentration of the polyvinyl alcohol is 5% to 25%, the concentration of the methacrylated hyaluronic acid solution is 2%, and the volume ratio of the two is 1:3-3:1.
[0010] Step 2: Treatment of the polypropylene patch: After ultrasonic cleaning and drying, the polypropylene patch is immersed in a photoinitiator solution in a light-proof condition before use. After the immersion, take it out and wipe it dry for use. Specifically, soak it in a 10% to 20% benzophenone solution for 15 to 30 minutes, take it out and wipe it dry for use.
[0011] Step 3: coating the pre-gel mixture on the surface of the polypropylene substrate: immersing the polypropylene patch in the gel precursor solution, irradiating each surface with ultraviolet light, initiating a free radical polymerization reaction through ultraviolet light, taking it out after irradiation, and washing away the liquid that has not gelled on the surface; Step 5: Treatment of polypropylene substrate: Freeze the polypropylene patch coated with the pregel mixture at -20°C for 12 hours; after taking it out, thaw it at room temperature. After a freeze-thaw cycle, the pregel mixture forms a uniformly distributed hydrophilic hydrogel coating on the surface of the polypropylene patch substrate.
[0012] The polypropylene patch coated with the hydrophilic hydrogel coating has the purpose of preventing adhesion at the abdominal surgical site, which is specifically manifested in its anti-inflammatory properties and ability to promote angiogenesis, based on the fact that the obtained patch has a hydrophilic composite hydrogel coating and a retained pore structure.
[0013] (1) Under ice bath conditions, methacrylic anhydride is added to an alkaline hyaluronic acid solution. With the help of methacrylic anhydride, a C=C double bond is introduced into the hyaluronic acid structure to obtain methacrylated hyaluronic acid. The modified hyaluronic acid can form a hydrogel in situ under the initiation of 365 nm ultraviolet light. On the other hand, it can reduce the impact on the pore structure of the polypropylene patch itself and improve the anti-adhesion effect of the polypropylene patch after surgery. It is highly practical, has a simple gelation process, and the operation steps are controllable, which is easy to mass-produce industrially.
[0014] (2) Polyvinyl alcohol and methacrylated hyaluronic acid solution were mixed to obtain a pre-gel mixture; the stability of the hyaluronic acid-based hydrogel was improved by adding polyvinyl alcohol. Under simulated physiological conditions, the composite hydrogel coating was stably present on the surface of the polypropylene patch for 30 days, which could fully block the direct contact between the polypropylene patch and the damaged tissue and play an anti-adhesion role. Compared with other anti-adhesion polypropylene patches, the retention of the pore structure can promote tissue repair.
[0015] (3) In terms of the selection of raw materials, both polyvinyl alcohol and hyaluronic acid have excellent biocompatibility. The prepared composite hydrogel can not only prevent the formation of postoperative adhesions, but also reduce inflammatory responses and promote the formation of new blood vessels. Beneficial Effects
[0016] The preparation method of the present invention is simple, the conditions are mild and easy to control. The prepared anti-adhesion polypropylene patch includes a mesh patch substrate and an anti-adhesion composite hydrogel coating. The composite hydrogel coating has good biocompatibility, can reduce inflammatory response, effectively prevent the formation of postoperative adhesion and promote the formation of new blood vessels. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Surface morphologies of pure reticulated polypropylene (V-PP), comparative example 1, comparative example 2, and polypropylenes of different formulations in Example 1; Figure 2 The water contact angle (WCA) diagram of pure network polypropylene (V-PP), comparative example 1, comparative example 2 and polypropylene with different formulations in Example 1; Figure 3 The stability of the gel part of polypropylene with different formulations on the patch surface in Comparative Example 1, Comparative Example 2 and Example 1; Figure 4 The degradation performance of the gel part of polypropylene with different formulations in Comparative Example 1, Comparative Example 2 and Example 1; Figure 5 Cytotoxicity test of pure reticulated polypropylene (V-PP), comparative example 1, comparative example 2 and polypropylene with different formulations in Example 1; Figure 6 is pure reticulated polypropylene (V-PP), and PVHM1- c -Digital photos of PP and L929 cells co-cultured; Figure 7 It is pure mesh polypropylene (V-PP), commercial anti-adhesion patch PLRM3 Ò And PVHM1- c -Digital photos of PP's in vivo anti-adhesion in animals; Figure 8 It is pure mesh polypropylene (V-PP), commercial anti-adhesion patch PLRM3 Ò And PVHM1- c - Anti-adhesion score of PP in animals; Fig. 9 It is pure mesh polypropylene (V-PP), commercial anti-adhesion patch PLRM3 Ò And PVHM1- c - Histological evaluation of PP implanted in animals 30 days later; Fig.10 It is pure mesh polypropylene (V-PP), commercial anti-adhesion patch PLRM3 Ò And PVHM1- c -Evaluation of angiogenesis 30 days after PP implantation in animals. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described in detail below in conjunction with comparative examples, embodiments and drawings.
[0019] A method for preparing a polypropylene patch coated with polyvinyl alcohol hydrogel, comprising the following steps: (1) Place the mesh polypropylene patch in a mixed solution of ethanol and dichloromethane (volume ratio 2:1) and stir and wash it three times, each time for 1 hour. After washing, dry it in a vacuum drying oven at 37°C; (2) Add 0.5 g polyvinyl alcohol (DP 1750 ± 50) into 10 mL of deionized water and stir to dissolve at 80 °C. (3) coating the polypropylene patch processed in step (1) with a layer of the polyvinyl alcohol solution dissolved in step (2) on both sides; (4) freezing the treated polypropylene patch obtained in step (3) at -20°C for 12 hours; (5) The polypropylene patch frozen in step (4) is taken out and thawed at room temperature to obtain a polypropylene patch coated with polyvinyl alcohol hydrogel.
[0020] A method for preparing a polypropylene patch coated with methacrylated hyaluronic acid hydrogel, comprising the following steps: (1) Place the mesh polypropylene patch in a mixed solution of ethanol and dichloromethane (volume ratio 2:1) and stir and wash it three times, each time for 1 hour. After washing, dry it in a vacuum drying oven at 37°C; then immerse it in a benzophenone acetone solution for 15 minutes. After the end, quickly remove it and wipe the surface dry for later use; (2) At 50°C, dissolve 0.5 g of sodium hyaluronate in 50 mL of deionized water. After complete dissolution, adjust the pH value to 8 using 5 mol / L sodium hydroxide solution. (3) adding 4.067 g of methacrylic anhydride to the hyaluronic acid solution prepared in step (2), stirring for reaction in an ice bath for 8 hours, then dropping icy ethanol for precipitation, and then centrifuging at 10,000 revolutions per minute in a high-speed centrifuge for 10 minutes, removing the supernatant to obtain a precipitate; placing the obtained precipitate in a dialysis bag, dialyzing it in water for 5 days, and freeze-drying it after the dialysis to obtain a sponge-like solid methacrylated hyaluronic acid; (5) Add 0.2 g of methacrylated hyaluronic acid into 10 ml of deionized water and dissolve at 50°C; place the polypropylene patch prepared in step (1) in the methacrylated hyaluronic acid solution and irradiate each side under 365 nm ultraviolet light for 1 hour. After irradiation, remove the polypropylene patch and gently rinse off the ungelled liquid on the surface with ultrapure water to obtain a polypropylene patch coated with methacrylated hyaluronic acid hydrogel. Example
[0021] A method for preparing a polypropylene patch coated with a hydrophilic composite hydrogel, comprising the following steps: (1) Place the polypropylene patch in a mixed solution of ethanol and dichloromethane (volume ratio 2:1) and stir and wash it three times, each time for 1 hour. After washing, dry it in a vacuum drying oven at 37°C. Before use, immerse the polypropylene patch in a benzophenone-acetone solution for 15 minutes. After the end, quickly remove it and wipe the surface dry for later use. (2) At 50°C, dissolve 0.5 g of sodium hyaluronate in 50 mL of deionized water. After complete dissolution, adjust the pH value to 8 using 5 mol / L sodium hydroxide solution. (3) adding 4.067 g of methacrylic anhydride to the hyaluronic acid solution prepared in step (2), stirring for reaction in an ice bath for 8 hours, then dropping icy ethanol for precipitation, and then centrifuging at 10,000 revolutions per minute in a high-speed centrifuge for 10 minutes, removing the supernatant to obtain a precipitate; placing the obtained precipitate in a dialysis bag, dialyzing it in water for 5 days, and freeze-drying it after the dialysis to obtain a sponge-like solid methacrylated hyaluronic acid; (4) At 50°C, 0.2 g of methacrylated hyaluronic acid was dissolved in 10 mL of deionized water. At 80°C, 0.5 g of polyvinyl alcohol was dissolved in 10 mL of deionized water. After the two solutions were completely dissolved, different volumes of the two solutions were taken according to Table 1 below and mixed evenly to obtain a gel precursor solution. Table 1 Formula of gel precursor solution Modified polypropylene patch 5% polyvinyl alcohol solution (mL) 2% Methacrylated Hyaluronic Acid Solution (mL) PVHM1--PP 7.5 2.5 PVHM2--PP 5 5 PVHM3--PP 2.5 7.5 (5) The polypropylene patch prepared in step (1) is placed in a gel precursor solution and irradiated under 365 nm ultraviolet light for 1 hour on each side. After irradiation, the patch is frozen at -20°C for 12 hours. The patch is taken out and thawed at room temperature to obtain a polypropylene patch coated with a hydrophilic composite hydrogel.
[0022] See also Figure 1, are surface morphologies of pure mesh polypropylene, comparative example 1, comparative example 2, and polypropylene patches prepared with different formulations in Example 1. The surface of pure mesh polypropylene monofilaments has gully-like textures of varying depths, while the surface of mesh polypropylene monofilaments with gel coating is smooth. The successful coating of the hydrogel coating can be observed from the cross-sectional scanning electron micrograph. Figure 2 , are the water contact angle results of the surfaces of pure mesh polypropylene, comparative example 1, comparative example 2, and polypropylene patches prepared with different formulations in Example 1. The water contact angle of the pure mesh polypropylene patch is 107.5°. After the polyvinyl alcohol hydrogel is coated in Comparative Example 1, the water contact angle is 34.7°; after the methacrylated hyaluronic acid hydrogel is coated in Comparative Example 2, the water contact angle is 39.3°; after the composite hydrogels of three different formulations are coated in Example 1, the PVHM1- c -PP, PVHM2- c -PP, PVHM3- c -PP, and their water contact angles were 37.4°, 39.6°, and 37.2°, respectively. Compared with pure mesh polypropylene, the hydrophilicity of the mesh polypropylene patch surface was significantly improved after being coated with different types of hydrogel coatings. This is because there are a large number of hydrophilic groups on the molecular chains of polyvinyl alcohol and hyaluronic acid, so the hydrophilicity of the modified polypropylene patch surface is significantly increased.
[0023] Example 2 Investigation of the stability of the hydrogel coating on the patch surface In order to fully exert the anti-adhesion effect, the anti-adhesion material should always be present between the damaged part and the polypropylene patch during the critical period of postoperative adhesion formation (within 14 days). The hydrogel coating part plays an anti-adhesion role in the anti-adhesion polypropylene patch prepared by the present invention. The stability of the hydrogel coating on the surface of the polypropylene patch was tested in PBS (pH=7.4) at two temperatures of 37°C and 40°C, see Figure 3 In the initial stage of immersion, the mass of the freeze-dried hydrogel increased due to swelling. As the immersion time increased, the mass change trend slowed down. Figure 3 It can be seen that in the PBS environment at 37℃ and 40℃, PVHM1- c -PP has better stability than other polypropylene patches. This is because a methacrylated hyaluronic acid gel layer is first formed in situ on the surface of the polypropylene patch by ultraviolet light-induced free radical polymerization, and then the polyvinyl alcohol forms a network structure through freeze-thaw to reinforce the initial gel layer. As the content of methacrylated hyaluronic acid increases and the content of polyvinyl alcohol decreases, the formed gel layer is not sufficiently reinforced, resulting in reduced stability. Since hyaluronic acid is easily degraded by hydrolysis or enzymatic reactions in the human body, the degradation performance of the gel coating was tested in a hyaluronidase solution, see Figure 4 ,PVHM1-c -The hydrogel coating on the PP surface exhibits the most suitable degradation performance, and the network structure formed by polyvinyl alcohol improves the stability of the methacrylated hyaluronic acid gel network. Therefore, in Table 1, the volume ratio of the polyvinyl alcohol solution to the methacrylated hyaluronic acid solution is preferably 3:1.
[0024] Example 3 Cytocompatibility Experiment Cell compatibility is one of the important indicators of biomaterials. Figure 5 , L929 cells were inoculated on the surface of pure mesh polypropylene, comparative example 1, comparative example 2, and polypropylene patches prepared with different formulas in Example 1, and the cell viability after culturing for 1, 3, 5, and 7 days, respectively, all of which were greater than 90%, indicating that the polypropylene patch prepared by the present invention has good cell compatibility. Inhibiting the adhesion of fibroblasts on the surface of implant materials is crucial to prevent the formation of postoperative adhesions. L929 cells were inoculated on the surface of the material and their adhesion behavior was observed, see Figure 6 As the culture time increases, the PVHM1- c On the surface of the -PP patch, cells grow in clusters and form multicellular spheres as the culture time increases. This is because the hydrophilicity of the surface of the polypropylene patch prepared by the present invention increases, and a hydration layer is formed on the surface of the gel layer, which hinders the adsorption of cell adhesion proteins and plays a role in preventing cell adhesion.
[0025] Example 4 Porosity Experiment The porous structure of the polypropylene patch itself is conducive to tissue ingrowth and integration with host tissue, which is beneficial to the PVHM1- c The pore structure of -PP was statistically analyzed, and its pore retention rate was 43.33%. It was implanted into a rat abdominal wall full-thickness defect model, and the original mesh polypropylene patch and the commercial anti-adhesion patch PLRM3 were implanted at the same time. Ò The in vivo anti-adhesion performance of these three patches was compared. Among them, the commercial anti-adhesion patch PLRM3 Ò It is a direct composite of the anti-adhesion film layer and the PP patch, with a pore retention rate of 0%. Figure 7 During the entire implantation period (30 days), the pure polypropylene group had severe adhesion, while the polypropylene patch in Example 1 did not have obvious adhesion. The adhesion degree was quantitatively scored, see Figure 8 , PVHM1- in Example 1 c -The adhesion score of the PP patch group was significantly lower than that of the other two groups. Fig. 9 HE and Masson staining showed a large number of inflammatory cells infiltrating around the pure polypropylene monofilament and excessive deposition of collagen fibers. ®Although the patch has an anti-adhesion effect, the completely lost pore structure is not conducive to the integration of the patch and the tissue, and a certain inflammatory response is shown. c -In the PP patch group, the inflammatory reaction around the monofilament was mild, and the collagen fibers were loose and regular in shape, with a smooth trend. Fig.10 Figure 3 shows the formation of new blood vessels in different material groups 30 days after implantation. There are fewer new blood vessels around the pure polypropylene patch monofilament, and fewer around the commercial anti-adhesion patch PLRM3. Ò The number of new blood vessels around the patch monofilaments increased, while the PVHM1- c -The number of new blood vessels distributed around the PP patch monofilament is the largest. In vivo implantation experiments show that the polypropylene composite material obtained by this preparation process can not only effectively isolate the original polypropylene patch from the internal organs and play a role in preventing adhesion, but also reduce the inflammatory response in the damaged tissue, promote the formation of new blood vessels, and facilitate the repair of damaged tissue.
[0026] The present invention first modifies hyaluronic acid to obtain methacrylated hyaluronic acid, then forms an initial gel layer in situ on the surface of a polypropylene patch with a gel precursor solution containing methacrylated hyaluronic acid and polyvinyl alcohol under ultraviolet irradiation, and then forms a gel reinforcement layer by freezing-thawing. By forming a composite hydrogel coating on the surface of a polypropylene patch in this way, the influence on the pore structure of the polypropylene patch itself can be reduced, and the integration of the patch material and the tissue can be improved. The prepared polypropylene patch can not only prevent the formation of adhesion, but also reduce inflammatory reactions, promote the generation of new blood vessels, and promote the repair of damaged tissues.
[0027] The specific implementation modes of the present invention are described above in conjunction with the accompanying drawings, but these descriptions cannot be understood as limiting the scope of the present invention. The protection scope of the present invention is defined by the attached claims, and any changes based on the claims of the present invention are within the protection scope of the present invention.
Claims
1. A highly stable medical polypropylene patch, characterized in that: include: A substrate and a composite hydrogel coating coated on the surface of the substrate; The substrate is mesh polypropylene; the hydrogel coating is prepared from polyvinyl alcohol and methacrylated hyaluronic acid by ultraviolet light-induced free radical polymerization and freeze-thaw method.
2. The method for preparing a highly stable medical polypropylene patch according to claim 1, characterized in that: Here are the steps: Step 1: Preparation of methacrylated hyaluronic acid (Growth factor–loaded sulfated microislands in granular hydrogels promote hMSCs migration and chondrogenic differentiation Acta Biomaterialia 166 (2023) 69-84; Anna Puiggalí-Jou et al.): (1) dissolving hyaluronic acid in water at room temperature to 50° C. and adjusting the pH value to 7.5 to 9 to obtain a hyaluronic acid aqueous solution; (2) adding methacrylic anhydride to the hyaluronic acid solution, stirring and reacting for 8 to 24 hours under ice bath conditions, then dropping ice ethanol to precipitate, and then centrifuging in a high-speed centrifuge to remove the supernatant to obtain a precipitate; (3) placing the obtained precipitate in a dialysis bag, dialyzing it in water, and freeze-drying it after the dialysis to obtain a sponge-like solid methacrylated hyaluronic acid; Step 2: Preparation of gel precursor solution: Under heating conditions, prepare methacrylated hyaluronic acid solution and polyvinyl alcohol solution respectively, mix the two solutions in proportion, and stir evenly to obtain gel precursor solution; Step 3: Treatment of the polypropylene patch: ultrasonically clean and dry the polypropylene patch, soak it in a photoinitiator solution under light-proof conditions before use, take it out and wipe it dry for later use; Step 4: coating the pre-gel mixture on the surface of the polypropylene substrate: immerse the polypropylene patch in the gel precursor solution, irradiate each surface with ultraviolet light, and initiate a free radical polymerization reaction through ultraviolet light. After the irradiation is completed, take it out and rinse off the liquid that has not gelled on the surface; Step 5: Treatment of polypropylene substrate: Freeze the polypropylene patch coated with the pregel mixture at -20°C for 12 hours; after taking it out, thaw it at room temperature. After a freeze-thaw cycle, the pregel mixture forms a uniformly distributed hydrophilic hydrogel coating on the surface of the polypropylene patch substrate.
3. The method for preparing a high-stable polypropylene patch according to claim 1, characterized in that: In step 2, the solvents of the polyvinyl alcohol and methacrylated hyaluronic acid solutions are water or phosphate buffer solution; the methacrylated hyaluronic acid solution is prepared at 50°C; and the polyvinyl alcohol solution is prepared at 80°C.
4. The method for preparing a high-stable polypropylene patch according to claim 1, characterized in that: In step 2, the concentration of the polyvinyl alcohol is 5% to 25%, the concentration of the methacrylated hyaluronic acid solution is 2%, and the volume ratio of the two is 1:3-3:
1.
5. The method for preparing a high-stable polypropylene patch according to claim 1, characterized in that: The photoinitiator solution is an acetone solution of benzophenone with a concentration of 10% to 20%; the immersion time is 15 to 30 minutes.
6. Use of the high-stability medical polypropylene patch according to claim 1 for preventing adhesion of surgical sites after surgery.
7. The use according to claim 6, characterized in that It is based on the anti-inflammatory properties and ability to promote angiogenesis of highly stable medical polypropylene patches.